Remitansi, Kesenjangan Tata Kelola, dan Absennya Representasi Pekerja Migran Perempuan di Daerah - Novalita Radiatie; Rini Archda Saputri (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2026)
This article examines the absence of representation of women migrant workers in Indonesian legislative institutions. This absence is ironic, given their significant contribution to the national economy. The study uncovers various reasons for the lack of representation of women migrant workers in legislative institutions, a reality analyzed as “empty political seats.” Using a qualitative approach, the study relies on secondary data from academic journals, books, research reports, mass media articles, and civil society organization publications. The analysis focuses on how the social construction, legal framework, and socio-economic conditions of women migrant workers contribute to inequality in political representation. The findings indicate that social stigma, limited access to political education and information, and economic vulnerability limit women migrant workers' political participation. The study also highlights how the political system, migration, and patriarchal culture reinforce the marginalization of women migrant workers in decision-making. The study recommends comprehensive systemic reform, including deconstructing social stigma, increasing access to political and economic education, and mainstreaming gender in the Indonesian political system.